Emerging Role Of Information And Communication Technologies In Modern Education: Issues & Concerns With Special Reference To Developing Economies - *Dr.Umesh Prasad, Dr.Soumitro Chakravarty (International Journal of Advanced Science and Technology, 2020)
The advent of Information and Communication Technology (ICT) across all sectors of life has brought about a revolution in the modern age. The impact of ICT has also brought about a paradigm shift in the fields of teaching and learning. There has been a great deal of interest among policy makers and researchers about the applications, scope and challenges of ICT in education and subsequently a great deal of research has been carried out in this field over the last few decades. However, the research has been quite broad in scope across both national and international dimensions. This working research paper aims towards understanding the key issues related to the existing and emerging role of ICT in modern education with special reference to the developing economies like India, based on a thorough review of literature on the subject across dimensions which have acted as a barrier for developing economies to reap the full potential benefits of ICTs in education and development itsuggests the steps and initiatives that are crucially important for developing countries and their respective governments in this regard.